Statistical Properties & Different Methods Of Estimation Of A New Extended Weighted Frechet Distribution. - et. al., Mahdi Wahhab Neamah , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we introduce a new distribution is called the extended weighted Frechet distribution, which we obtain by applying the Azzalini method and deduced some statistical properties such as mean, variance, coefficients of variation, coefficient of skewness, and coefficient of kurtosis. The parameters of the new distribution were estimated by the following estimation methods: Maximum Likelihood Method (MLE) and percentile method. We used the Monte Carlo simulation to compare the performances of the proposed estimators obtained through methods of estimation.